Istota controllingu w literaturze polskiej i zagranicznej - Bednarek, Piotr (Definition of Controlling in Polish and Foreign Literature, 2006)
This paper is an effort to formulate the definition of controlling. It starts with some simple explanations of the word. Then it focuses on its historic and etymologic meaning in four countries: the United States of America, Great Britain, Germany, and Poland. Based on that, the author concludes that controlling is rather a way of dealing with the specific problems, that were faced by specially big companies and other organizations in the last century. Finally some current efforts to formulate the real definition of the term were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 82-89